Ixodes ricinus as vector and reservoir of Borrelia burgdorferi in an urban environment - Rajković Dragana V.; Jurišić A.D. (Archives of Biological Sciences, 2005)
As specific arthropods, ticks in urban environments transmit the agents of dangerous contagious diseases endangering human and animal health. They are vectors of numerous infective agents that cause serious diseases of animals such as babesiosis and ehrlichiosis. Tick populations maintain and transmit an increasing number of different infective agents. In regard to the human population, they transmit the agents of tick encephalitis, Omsk hemorrhagic disease, Crim-Congo hemorrhagic disease, Kyasa-nur forest fever, ixodid fever, Q fever, Rocky Mountain spotted fever, tularemia, Siberian tick typhus and Lyme disease the last of which according to acarological references has become the dominant zoonosis in over 140 of the world's countries. In urban environments ticks represent problem both for their epidemiological significance and as organisms whose presence disturbs people during their work and rest. In Europe, the two most frequent species and Ixodes ricinus and Ixodes persulcatus. Both species have a wide spectrum of hosts.